Quantitative Analysis of Illusory Movement: Spatial Filtering and Line Localization in the Human Visual System. (December 2014) - Jansonius, Nomdo M; Stam, Lucas; de Jong, Tim; Pijpker, Ben A
A narrow bar or line (width around 1 arcmin) between two fields of which the luminances are sinusoidally and in counterphase modulated in time appears to make an oscillatory movement. It is possible to annihilate this illusory movement with a real movement and thus to analyze this phenomenon quantitatively. Confirming previous studies, the amount of illusory movement (amplitude typically 10 arcsec) was proportional to the modulation depth of the fields and inversely proportional to the line width and the line contrast. The amount of illusory movement increased with defocus, a lower mean luminance, and eccentricity. The experimental results could be explained by a model that includes a linear low-pass spatial filter. For a Gaussian spatial filter, the standard deviation as derived from the experimental results was 1.1 arcmin (1.0–1.3 arcmin) (median with range of four observers) for well-focused, photopic, foveal viewing. We explored various criteria for line localization in the model (extremes and zero-crossings of Gaussian derivatives).